2016
DOI: 10.1093/mnras/stw800
|View full text |Cite
|
Sign up to set email alerts
|

nIFTy galaxy cluster simulations – II. Radiative models

Abstract: We have simulated the formation of a massive galaxy cluster (M crit 200 = 1.1×1015 h −1 M ) in a ΛCDM universe using 10 different codes (RAMSES, 2 incarnations of AREPO and 7 of GADGET), modeling hydrodynamics with full radiative subgrid physics. These codes include Smoothed-Particle Hydrodynamics (SPH), spanning traditional and advanced SPH schemes, adaptive mesh and moving mesh codes. Our goal is to study the consistency between simulated clusters modeled with different radiative physical implementations -su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 137 publications
(171 reference statements)
2
40
0
Order By: Relevance
“…In Section 3, we introduced the different hot gas profiles necessary to estimate the hydrostatic mass profile of a cluster. Comparing the results from the different runs, it was found that at low mass (8 × 10 13 < M 500,true [M ] < 3 × 10 14 ) the impact of the subgrid physics was greater than the effects of changing the SPH flavour (as was also reported by Sembolini et al 2016b). However, when moving to the most massive clusters (M 500,true 10 15 M ), the effect of changing the SPH flavour can be seen in the cluster cores, whereas there is less of an effect from changing the subgrid physics as the cluster potentials are too deep.…”
Section: Hydrostatic Mass Biassupporting
confidence: 54%
See 3 more Smart Citations
“…In Section 3, we introduced the different hot gas profiles necessary to estimate the hydrostatic mass profile of a cluster. Comparing the results from the different runs, it was found that at low mass (8 × 10 13 < M 500,true [M ] < 3 × 10 14 ) the impact of the subgrid physics was greater than the effects of changing the SPH flavour (as was also reported by Sembolini et al 2016b). However, when moving to the most massive clusters (M 500,true 10 15 M ), the effect of changing the SPH flavour can be seen in the cluster cores, whereas there is less of an effect from changing the subgrid physics as the cluster potentials are too deep.…”
Section: Hydrostatic Mass Biassupporting
confidence: 54%
“…• Within the fitting region (0.15 − 1.5 r 500,true ), the CELR-B and CELR-E density, temperature and pressure profiles ( Fig.s 5-7 respectively) become more comparable as the mass of the clusters increases. This shows how differences in the subgrid models are more important at low mass (Sembolini et al 2016b). The effect of changing the SPH flavour (specifically the inclusion of artificial conduction) is most evident in the cores of the most massive clus-ters, shown by the median profiles in Section 3.…”
Section: Summary and Future Workmentioning
confidence: 85%
See 2 more Smart Citations
“…However, an important caveat is that predictions of current simulations are often sensitive to the details of the 'sub-grid' modelling of important feedback processes Sembolini et al 2016;McCarthy et al 2016), as we will demonstrate here as well. Therefore, continual confrontation of the simulations with the observations (via production of realistic synthetic observations of the simulations) is also needed to test the realism of the former.…”
mentioning
confidence: 69%